Antithrombotic Therapy in Patients With Atrial Fibrillation and Coronary Artery Disease Undergoing Percutaneous Coronary Intervention. Issue 2 (August 2019) - Mishra, Abhishek; Singh, Maninder; Acker, Warren W.; Kamboj, Sukriti; Sporn, Daniel; Stapleton, Dwight; Kaluski, Edo
Abstract : Aim: The objective of this article is to review the contemporary literature on the use of antithrombotic therapy in patients with atrial fibrillation (AF) and coronary artery disease after undergoing percutaneous coronary intervention (PCI). Special consideration was given to the type and duration of therapy, treatment strategies for the elderly (≥65 years of age), and strategies to reduce bleeding. Methods: Relevant studies were searched through MEDLINE/PubMed, Web of Science, Cochrane Library, ClinicalTrials.gov, and Google Scholar. Of the 236 publications retrieved, 76 were considered relevant including 35 randomized controlled trials, 17 meta-analyses, 16 observational studies, and 8 published major guidelines. Results: Most trials, meta-analyses, and guidelines support 1 month of triple therapy (TT) with an oral anticoagulant (OAC), dual antiplatelet agents (DAPT) with aspirin (ASA)/clopidogrel, and, afterward, dual therapy (DT) with OAC and single antiplatelet agent for an additional 11 months, or alternatively DT alone for 12 months after PCI. Individual consideration is given to the risk and impact of stent thrombosis (ST), thromboembolism, and bleeding. Several trials and meta-analyses have also suggested that shorter DAPT duration (⩽6 months) may be safer than longer therapy (≥6 months) when weighing the risk of bleeding with ischemic outcomes, especially with newer generation drug-eluting stents. The selective use of proton-pump inhibitors in patients prone to gastrointestinal bleeding who are subjected to prolonged exposure with TT or DT may be beneficial. In the elderly, the risk of bleeding from TT, compared with DT, outweighs the benefit of reducing ischemic events. Conclusions: In conclusion, tailoring therapy to the individual patient is recommended considering the ischemic and bleeding risk as well as the risk of thromboembolism. For most patients with AF, 1 month of TT and subsequently DT for additional 11 months are recommended. Abstract : Supplemental Digital Content is Available in the Text.